Cooperation between the state professional schools of higher education and local government units in the context of local socio-economic development - Adamowicz, Mieczysław; Pyra, Mariusz (Współpraca państwowych wyższych szkół zawodowych z jednostkami samorządu terytorialnego w kontekście lokalnego rozwoju społeczno-gospodarczego, 2020)
Universities operate in a complicated environment, in which one of the important elements are, in addition to business, local government authorities. The purpose of the article is to characterize the cooperation of local government units (LGU) with state professional schools of higher education (SPSHE) in order to create local socio-economic development. The object of research are SPSHE from the Lubelskie Voivodeship together with LGU in which they are located. The stage of collecting primary data included surveys among LGU and SPSHE employees, which were carried out as part of broader research for the doctoral dissertation of one of the authors of the article. The survey research method was used. Research shows that such cooperation still faces numerous barriers. There is a need to establish closer cooperation between LGU and SPSHE, primarily in the area of designing local development by local government authorities in the region, as well as increasing the activity of SPSHE and LGU in cluster structures
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 5-15
Keywords: SPSHE; LGUs; development; cluster; cooperation; PWSZ; JST; rozwój; klaster; współpraca